ANALISIS KINERJA ORGANISASI DENGAN PENDEKATAN BALANCED SCORECARD DI RUMAH SAKIT IBNU SINA MAKASSAR - Sumarni, Sumarni (Unnes Journal of Public Health, 2017)
Abstrak Balanced Scorecard memberi kerangka kerja untuk penerjemahan strategi ke dalam kerangka operasional.Kinerja adalah hasil kerja yang dapat dicapai seseorang atau sekelompok orang dalam suatu organisasi sesuai dengan wewenang dan tanggung jawab masing-masing dalam rangka mencapai tujuan organisasi. Hasil penelitian menunjukkan berdasarkan perspektif pembelajaran dan pertumbuhan berada pada kategori tinggi. Berdasarkan perspektif proses bisnis internal terkait pencapaian standar pelayanan minimal dan prosedur pelayanan berada pada kategori tinggi. Berdasarkan perspektif pelanggan dengan dimensi pengukuran kepuasan pelanggan, jumlah pelanggan komplain, layanan purna jual, dan retensi pelanggan berada pada kategori tinggi. Kualitas jasa yang dihasilkan oleh rumah sakit maka akan menjadikan customer repet buyer dan akan memberitahu rekan mereka mengenai kepuasan mereka terhadap jasa rumah sakit, sehingga diharapkan akan menambah cutomer baru.Untuk  perspektif keuangan berada pada kategori tinggi.    Kata kunci: Balanced Scorecard, Pengukuran kinerja.   Abstract The Balanced Scorecard provides a framework for translation of strategies into the operational framework. Performance is the work that a person or group of people in an organization can achieve in accordance with their respective powers and responsibilities in order to achieve the organization's objectives.Based on the performance of research, in terms of perspective of learning and growth, Ibnu Sina Hospital was classified to have high category. Based on the perspective of internal business processes related to the achievement of minimum service standards and service procedures, Ibnu Sina Hospital was also classified into the high category. Having high quantity of services, the hospital was expected to have an impact on the customer choice to come back. Based on the customer's perspective to the dimensions of customer satisfaction measurement, the number of customer complaints, after sales service and customer retention were also classified into high category.Based on the done calculations, the financial perspective was classified into the high category.   Keywords: Balanced Scorecard, Performance Measurement. Based on the performance of research, in terms of perspective of learning and growth, Ibn Sina Hospital was classified to have high category, which means its employees possess high satisfaction and commitment to work. Based on the perspective of internal business processes related to the achievement of minimum service standards and service procedures, Ibn Sina Hospital was also classified into the high category. Having high quantity of services, the hospital was expected to have an impact on the customer choice to come back. Based on the customer's perspective to the dimensions of customer satisfaction measurement, the number of customer complaints, after sales service and customer retention were also classified into high category. The quality of services produced by the Hospital will make the ‘customer repeat buyer’ and will inform their colleagues about their satisfaction with the hospital services, which is expected to add a new customer. Meanwhile, financial state performance in Ibn Sina Hospital based on revenue trend reached an increase up to 729.0% with Return On Investment amounting to -0.24, Income Statement was still showed a loss (deficit) of Rp. 995 310 037, but it is still within reasonable limits due to nominal assets which had already included the construction in progress of the new Ibn Sina Hospital's building (not yet operating). The measurements in ‘Fixed Assets Turnover’ obtained 0.04, while the ‘Inventory Turnover’ amounted up to 2,3. Based on the done calculations, the financial perspective was classified into the high category.